The ground state of the &quotfrozen&quot electron phase in two-dimensional narrow-band conductors with a long-range interelectron repulsion. Stripe formation and effective lowering of dimension - Slutskin, A. A.; Slavin, V. V.; Kovtun, H. A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
In narrow-band conductors a weakly screened Coulomb interelectron repulsion can supress narrow-band electrons` hopping, resulting in formation of a &quotfrozen&quot electron phase which differs principally from any known macroscopic self-localized electron state including the Wigner crystal. In a zero-bandwidth limit the &quotfrozen&quot electron phase is a classical lattice system with a long-range interparticle repulsion. The ground state of such systems has been considered in the case of two dimensions for an isotropic pair potential of the mutual particle repulsion. It has been shown that particle ordering into stripes and effective lowering of dimension resides universally in the ground state for any physically reasonable pair potential and for any geometry of the conductor lattice. On the basis of this fact a rigorous general procedure to describe the ground state fully has been formulated. Arguments have been adduced that charge ordering into stripes in high-Tc superconductors testifies to the presence of a &quotfrozen&quot electron phase in these systems.